The impact of supervision and educational support in improving the performance of teachers in the first three grades and the impact on improving the reading skills of their students. - Khaled, Hasan (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of this study was to reveal the impact of supervision and educational attribution in improving the performance of the teachers of the first three grades and to improve the reading skills of their students. The study found that there were statistically significant differences between the tribal and remote applications in all sub-competencies and the total degree of teachers. The differences were in favor of the post application. The mathematical averages for the post application ranged from (3,41-3,88). The performance skills related to planning the lesson (3.88), while the "performance skills related to the evaluation" ranked last with an average of (3.41), and the general arithmetic mean of the fields (3.55). Table (1) shows that there are statistically significant differences at the level of significance (0.05 = α) between the tribal and remote applications in all sub-performance skills and the total score, and the differences were in favor of the post-application of teachers. The results of the reading skills test showed statistically significant differences between the tribal and remote applications in all secondary competencies and the total score of students. The differences were in favor of the post application. The mathematical averages for the post application ranged between (2.03-3.65) For learning to read "ranked first with the highest average score of (3.65), while" fourth level of learning to read "in the last place with an average of (2,03), and the arithmetic mean of the total score (2.97). There were also statistically significant differences at the level of significance (0.05) (α) between the tribal and remote applications Performance and skills sub-class college, came the differences in favor of the dimensional application for students.